Ménage à Trois: Unraveling the Mechanisms Regulating Plant–Microbe–Arthropod Interactions. (December 2020) - Gruden, Kristina; Lidoy, Javier; Petek, Marko; Podpečan, Vid; Flors, Victor; Papadopoulou, Kalliopi K.; Pappas, Maria L.; Martinez-Medina, Ainhoa; Bejarano, Eduardo; Biere, Arjen; Pozo, Maria J.
Abstract : Plant–microbe–arthropod (PMA) three-way interactions have important implications for plant health. However, our poor understanding of the underlying regulatory mechanisms hampers their biotechnological applications. To this end, we searched for potential common patterns in plant responses regarding taxonomic groups or lifestyles. We found that most signaling modules regulating two-way interactions also operate in three-way interactions. Furthermore, the relative contribution of signaling modules to the final plant response cannot be directly inferred from two-way interactions. Moreover, our analyses show that three-way interactions often result in the activation of additional pathways, as well as in changes in the speed or intensity of defense activation. Thus, detailed, basic knowledge of plant–microbe–arthropod regulation will be essential for the design of environmentally friendly crop management strategies. Highlights: Plant‐microbe‐arthropod (PMA) interactions have important impacts on plant fitness, and recent studies shed light on how plants regulate responses in such complex interactions. Biosynthetic pathways for the production of defensive and signaling compounds, and the corresponding signaling modules (mostly related to phytohormones) are key regulators both in interactions of the plant with either microbes or arthropods (two-way interactions), or when exposed to both (PMA; three-way interactions). Most signaling modules regulating two-way interactions of plants with microbes or arthropods also operate in three-way PMA interactions, but changes in their speed or intensity (e.g., defense priming) and/or activation of additional pathways frequently occur. These differences shape the outcome of PMA interactions and may have implications for ecologically based crop protection.